Anterior cruciate ligament injury profile in female elite Italian basketball league - Benis, R.; La Torre, A.; Bonato, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: In female basketball athletes anterior cruciate ligament (ACL) injury is the most frequent lower limb injury. Because it is very difficult to get a clear picture of the risk inherent in elite female Italian basketball players, we designed an observational study with a retrospective case-series design with the aim to investigate the incidence of ACL injury in elite Italian basketball league.